Pain management in hospitalized infants: recommendations for achieving the Sustainable Development Goals - Danton Matheus de Souza; Caroline Knoner Monteiro; Lisabelle Mariano Rossato (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to assess pain management in infants in a Neonatal Intensive Care Unit (NICU) and discuss its articulation with the Sustainable Development Goals, with a focus on promoting neonatal well-being. Method: a documentary study, retrospective in nature and quantitative approach, conducted in a NICU of a public hospital in Paraná, Brazil, between January and July 2022, with 386 medical records of infants, hospitalized for more than 24 hours, between 2019 and 2021. Data were subjected to descriptive and inferential analysis, considering p-value<0.05 as a statistical difference. National ethical guidelines were respected. Results: all infants underwent at least one painful procedure, but only 13.7% had documented pain. Pharmacological interventions, such as fentanyl (25.9%), and non-pharmacological interventions, such as breastfeeding encouragement (86%) were used. Only 2.8% were reassessed. Conclusion: there was a devaluation of neonatal pain management that may perpetuate neonatal well-being and sustainable development.